2008
DOI: 10.1093/humrep/den188
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index: impact on IVF success appears age-related

Abstract: In younger patients undergoing IVF, BMI has a significant negative impact on fertility that diminishes as patients reach their mid thirties. After Age 36, BMI has a minimal impact on fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
5
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 20 publications
3
92
5
4
Order By: Relevance
“…Additionally, we did not observe an association between female BMI and ART success. However, as shown by Sneed et al, it is likely that the impact of BMI on ART is only manifested at younger female ages, whereas after age 36 the effect of chronological aging appears to dominate any BMI effect [30]. We did not have sufficient power to consider the relationship between female BMI and ART outcome in detail; however, among women younger than 32, there was a suggestion for lower female BMI in successful couples.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Additionally, we did not observe an association between female BMI and ART success. However, as shown by Sneed et al, it is likely that the impact of BMI on ART is only manifested at younger female ages, whereas after age 36 the effect of chronological aging appears to dominate any BMI effect [30]. We did not have sufficient power to consider the relationship between female BMI and ART outcome in detail; however, among women younger than 32, there was a suggestion for lower female BMI in successful couples.…”
Section: Discussionmentioning
confidence: 79%
“…Although studies on the effects of obesity on ART have produced conflicting results, a recent metaanalysis of 21 studies concluded that women with BMI greater than 25 kg/m 2 had a significantly lower chance of clinical pregnancy as compared with normal weight women [29]. A potential breakthrough in understanding the precise relationship between obesity and ART success came from a recent study showing that at younger ages high female BMI had a pronounced negative influence on fertility, but after age 36, body mass had a minimal impact on fertility [30]. In contradistinction to the avalanche of data on female obesity and ART, knowledge on the influence of male body mass on IVF success is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In Erel et al, 2009 a literature review was performed difference between patients with different BMI. Zander -Fox et al, 2012, Singh et al, 2012, Vilarino et al, 2011, Bellver et al, 2010and Sathya et al, 2010 have not Sneed et al, 2008, showed that the interaction between however, BMI alone had no apparent effect. This had a greater impact on patients under 36 years, because in older women age became the most important factor.…”
Section: Number Of Oocytes Retrievedmentioning
confidence: 95%
“…One was the study of Veleva et al (2008) , which showed that the BMI graph curve that represents how BMI affects the miscarriage rate is U-shaped, meaning that patients of low weight also has their increased risk, independent of patient age ( Figure 3 ). Moreover, the revision of Rittenberg et al, 2011 revealed increased miscarriage rate in 14 studies (RR 1.36, 95 % CI 1.13 to 1.64, p et al, 2010, despite the rate being increased, this increase was not significant, as in Vilarino et al, 2011, Zhang et al, 2010and Sathya et al .,2010. Sneed et al, 2008 showed that miscarriage rate is not directly affected by BMI, but by the interaction between BMI and age, with age the main determining factor.…”
Section: Miscarriage Ratementioning
confidence: 96%
See 1 more Smart Citation